FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT GENERASI MILENIAL DALAM MENGGUNAKAN MOBILE BANKING (studi kasus Kelurahan Indralaya Mulya) - Hidayani; Melati (LA RIBA: Jurnal Perbankan Syariah, 2022)
This study aims to find out how the perceptions of the millennial generation use mobile banking in Indralaya Mulya Village, and to find out what factors influence the interest of the millennial generation in using mobile banking in Indralaya Mulya Village. The method used is a qualitative research method, the type of research used in this research is a type of field research (field research) which is descriptive qualitative, the data analysis used is using inductive thinking methods. The results of this study note that the perceptions of the millennial generation in Indralaya Mulya Sub-District indicate that their perceptions of mobile banking are positive in the sense that mobile banking provides the best service and is in accordance with their desires or interests in terms of using mobile banking, and factors that influence There are two millennial generations of interest in using mobile banking in Indralaya Mulya Village, namely internal factors (personality, motivation, attitudes and beliefs, lifestyle, and religion) and external factors (service, promotion and location). The conclusion in this study is that the perceptions felt by the millennial generation in Indralaya Mulya Village are in accordance with their wishes or interests in terms of using mobile banking, and the millennial generation in Indralaya Mulya Village are interested in using sharia mobile baking.